Faktor-Faktor Yang Mempengaruhi Peranan Perempuan dalam Budaya Bali di Desa Bali Sadhar Selatan Kecamatan Banjit Kabupaten Way Kanan - Widiastri, Ni Luh Kadek; Syarief, Yuniar Aviati; Rangga, Kordiyana K; Ibnu, Muhammad (Fakultas Pertanian, Universitas Lampung, 2024)
This study aims to identify and describe the factors that influence the role of women farmers and the view of Balinese culture on the role of women. The research was carried out in March 2022-April 2022 in South Bali Sadhar Village, Banjit District, Way Kanan Regency. The informants in this study were female farmers and male farmers who worked in the lowland rice sector with a total of 12 people. The approach used in this research is a qualitative approach with a research method, namely case studies. The results showed that the factors that influence the role of women are family factors, economic pressure factors, education factors and habit factors. This view of Balinese culture on the role of women is considered positive, because activities carried out in accordance with awig-awig (customary regulations) and work are an obligation to carry out dharma (goodness/truth) in accordance with Hindu religious teachings. Keywords: Factors, Role of Women, Balinese Culture